(untitled) (BIS Humanities and Social Science, 2025)
This study explores the strategic role of the Legal Aid and Consultation Institute (LBKH) at the Faculty of Law, University of Muhammadiyah Sukabumi (UMMI), in enhancing access to justice for the underprivileged community in Sukabumi, Indonesia. Legal aid is a constitutional right guaranteed under Article 28D and Article 34 of the 1945 Constitution, yet its implementation remains uneven in local regions. Employing an empirical-juridical method, this research draws upon interviews with law enforcement officials, local government representatives, and social institutions to evaluate the effectiveness of LBKH’s services. The findings reveal that legal aid remains constrained by limited institutional coordination, low legal awareness, and a lack of trained paralegals at the community level. The study proposes a collaborative framework linking LBKH, village authorities, and law enforcement agencies to ensure more effective delivery of justice. Strengthening the legal literacy of citizens and building sustainable community-based legal aid networks are critical to promoting equality before the law and realizing the vision of a just and law-abiding society.